Fatty acid vesicles acting as expanding horizon for transdermal delivery. (17th February 2017) - Kumar, Lalit; Verma, Shivani; Kumar, Sanjeev; Prasad, Deo Nandan; Jain, Amit Kumar
Abstract: The body is protected against the external environment by the skin due to its physical barrier nature. Stratum corneum composed of corneocytes surrounded by lipid region performs a major barrier function as it lies in the uppermost area of skin. Alteration in barrier function, increase in permeability, and disorganization of stratum corneum represent diseased skin. Drugs applied to the diseased skin should induce a local effect at the site of application or area close to it along with cutaneous absorption rather than percutaneous absorption. Conventional formulations like ointments, gels, and creams suffer from the drawback of limited local activity. For the enhancement of drug penetration and localization of the drug at the site of action approaches explored are liposomes, niosomes, ethosomes microparticles, and solid lipid nanoparticles. Vesicles composed of fatty acids like oleic acid and linoleic acid represent the new approach used for transdermal penetration and localization. In this review article, our major aim was to explore the applications of fatty acid vesicles for transdermal delivery of various bioactives.